Perancangan Sistem Informasi Percetakan Sablon Berbasis Website Menggunakan Metode Waterfall Pada Tangsware Industri - Mustakim, Nurul (CV. Shofanah Media Berkah, 2025)
The transformation of societal lifestyles in the digital era has influenced the way consumers shop, with information technology playing a crucial role in simplifying the process. Printing and garment businesses have also adapted to these developments, seeking to utilize innovations to expand marketing and streamline the ordering process. Tangswear Industri, a garment company established since 2015, currently relies on manual business processes in serving customers, leading to frequent errors in order recording and design discrepancies. Additionally, sales are inconsistent as they are primarily marketed through word of mouth. To address these issues, the researcher has designed a web-based information system for Tangswear Industri. This system not only serves as an online ordering platform but also functions as a gallery for organizing designs. The Waterfall development method is employed with the hope of overcoming constraints, improving order efficiency, and attracting customers from outside Tangerang.